Systematic review on role of miRNAs In AMI of young adults - Muhammad Musa, Nurul Ashikin; Abdullah, Nor Zamzila; A Talib, Noorlelawati; Abd Fuaat, Azliana; Abdullah, Aszrin (International Journal Of Allied Health Sciences, 2021)
Acute myocardial infarction (AMI) is the leading cause of death worldwide. In Malaysia, people are getting AMI at younger age compared to well-developed countries. The role of microRNA (miRNA) in pathogenesis of AMI is not well elucidated and its involvement in young population has not been studied. The systematic review performed using available electronic databases and also previous reviews. The databases were broad search and began with the generic terms to identify search terms that were relevant. Databases including PubMed, Science Direct and Medline were searched between January 2010 and December 2020 for this systematic review. A total of 97 articles found. Only 1 article showed that the research was done in young AMI population. 13 miRNAs were found to be upregulated and 16 downregulated in young acute coronary syndrome (ACS) patient, which included both ST elevation myocardial infarction (STEMI) and non-ST elevation myocardial infarction (NSTEMI). miRNA 183-5p was significantly upregulated in ACS patients with NSTEMI whereas miRNA 134-5p, miRNA 15a-5p and let 7i-5p were significantly downregulated in patients with STEMI compared to healthy control. Plasma miRNA 183-5p, miRNA 134-5p, miRNA 15a-5p and let 7i-5p were dysregulated in STEMI and NSTEMI where they can potentially be used to discriminate the two ACS forms in future study.